Emerging worker project - Jentzsch, Keith, author; Voss, Gary Wayne, advisor; Lundberg, Thomas R., committee member; Kokoska, Mary-Ann, committee member; Sparks, Diane Carol, committee member (Colorado State University. Libraries, 2007)
To view the abstract, please see the full text of the document.
Keywords: mixed media; Installations (Art) -- 21st century